Improving the Quality of Public Services through Bojonegoro Regency Public Service Mall Innovation - Deby Eprilianto; Trenda Aktiva Oktariyanda; M. Noer Falaq Al Amin; Melda Fadiyah Hidayar; Yuyun Eka Kartika Sari; Nur Fadillah Sebti Sulistiana (Journal La Sociale, 2023)
One of the efforts made by Bojonegoro Regency to improve service quality is by presenting a Community Service Mall. The aim of this research is to determine the improvement in the quality of public services with Public Service mall innovations in Bojonegoro Regency. The type of research used in this research is quantitative through structured interviews, direct observation and analysis of related documentation. The findings from this research state that in the Leadership aspect, the Head of the Investment and One-Stop Service Service carries out a democratic and transformative leadership style. From the management sector, we have developed technology-based services to make things easier for residents. In terms of risk management, mitigate problems from an early age by repairing the internet network. From the human capital aspect, existing human resources meet academic qualifications, are experienced and competent. From a technological perspective, services have been developed and can be easily accessed through various applications. This research concludes that the existence of the Public Service Mall in Bojonegoro Regency is running in accordance with orders from the Ministry of State Apparatus Empowerment and Bureaucratic Reform to present the latest public service innovations that are modern, effective and efficient.